PEMANFAATAN TUMBUHAN BAMBU UNTUK MENINGKATKAN KREATIVITAS GENERASI MUDA - Hadi Susilo, Joko; Handayani, Tri Astuti; Rahmawati, Laily Agustina; Astuti, Hartiningsih; Endang; Suprastiyo, Ahmad; Erwanto (Universitas Kadiri, 2023)
The purpose bamboo trees to have economic value. The method used in this activity is PAR (Participatory Action Research). PAR has three words that are always related to one another, namely participation, research, and action. All research must be implemented in action. PAR-based research is designed to examine something in order to change and make improvements to it. The results of theassistance explained that the education carried out was well received by the target group with the evaluation results that there were obstacles encountered in utilizing bamboo trees as creativity with economic value due to the interests and desires of the target group, lack of motivation and due to the impact of changing lifestyles drastically so that one looks at the benefits of bamboo trees and the results of education and discussion it can be explained that the bamboo tree craft made is a chicken cage because it suits the needs of the village community in general. Meanwhile, the implementation process of making crafts can run smoothly and with the constraints that the target group still does not understand the agreed systematics of making crafts.